Chrysis mediadentata Linsenmaier 1951 - Paukkunen, Juho; Rosa, Paolo; Soon, Villu; Johansson, Niklas; Ødegaard, Frode (Zenodo, 2014)
14. Chrysis mediadentata Linsenmaier, 1951 Chrysis ignita var. mediadentata Linsenmaier 1951: 75. Lectotype ♂ (designated by Linsenmaier 1959: 157); Switzerland: Wallis (NMLS) (examined) ( Chrysis ignita group). Remarks. The species has been reported from Finland by Valkeila (1962: 64, as C. ignita mediadentata ), Valkeila et al. (1963: 40, as C. ignita mediadentata ), Silfverberg (1981: 61), Vikberg (1986b: 68) and Ranta (2012: 33), from Norway by Erlandsson (1971: 88), Artsdatabanken (2010) and Rosa & Soon (2012), and from Sweden by Erlandsson (1971: 88), Janzon (1983: 171), Nilsson (1991: 86) and Rosa & Soon 2012 (as doubtful). All checked specimens have turned out to be incorrectly determined. A large proportion of them belong to an unknown taxon, which is closely related to C. ignita and C. impressa (see Chrysis sp.), but many belong to other species of the ignita group. Apparently, the distribution of C. mediadentata does not reach the Nordic and Baltic countries in Europe. The closest confirmed record is from northern Germany (Jakobs & Kornmilch 2007). Published as part of Paukkunen, Juho, Rosa, Paolo, Soon, Villu, Johansson, Niklas & Ødegaard, Frode, 2014, Faunistic review of the cuckoo wasps of Fennoscandia, Denmark and the Baltic countries (Hymenoptera: Chrysididae), pp. 1-67 in Zootaxa 3864 (1) on page 53, DOI:10.11646/zootaxa.3864.1.1, http://zenodo.org/record/4930433